Land Use/Land Cover Changes in Jirang Community and Rural Development Block of Ri Bhoi District, Meghalaya, North East India and their Future Implications - Kar, Mrityunjay; Tynsong, H.; Dkhar, M. (Indian Forester, 2023)
The study of changes in land use and land cover (LULC) in Jirang Community and Rural Development Block is critical for the area’s long-term development, planning, monitoring and management. The study made use of remote sensing and GIS tools. Using the Unsupervised Classification Technique, the Landsat Satellite Images utilized in the study have been classified into three key classes: forest land, agricultural land, and built-up/mining area. From 1990 to 2016, dynamic changes in the LULC pattern revealed that forest and agricultural land fell by 1 per cent (8.54 Km2 ) and 0.76 per cent (6.5 Km2), respectively, while built-up/mining area expanded by 1.76 per cent (15.04 Km2). According to the Markov Chain model, between 2016 and 2042, the forest and agricultural land would reduce by 1.48 per cent (12.68 Km2) and 0.12 per cent (1.06 Km2), respectively, while the built-up/mining area would expand by 1.60 per cent (13.74 Km2). The findings show that the area is influenced by development activities in the area, which have direct consequences for the area’s natural resources.